2009
DOI: 10.1158/1541-7786.mcr-08-0227
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Matrix-Induced Gene Expression in Human Breast Cancer Cells

Abstract: Extracellular matrix (ECM) molecules modify gene expression through attachment-dependent (focal adhesion-related) integrin receptor signaling. It was previously unknown whether the same molecules acting as soluble peptides could generate signal cascades without the associated mechanical anchoring, a condition that may be encountered during matrix remodeling and degradation and relevant to invasion and metastatic processes. In the current study, the role of ECM ligand-regulated gene expression through this atta… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 50 publications
1
24
1
Order By: Relevance
“…Soluble ECM ligands also induce intracellular signaling and modulate cell behavior in solid tumors. Soluble ColI has been shown to influence TGF␤ receptor signaling and gene expression in breast cancer cells (38,39), and soluble integrin ligands such as ColI also rescue neuroblastoma cells from apoptosis under nonadherent conditions (40). ECM remodeling and degradation by metalloproteinases, which is associated with cancer growth and invasion, is likely to lead to the release of ECM components that can act as "soluble" pep- tides within the tumor microenvironment.…”
Section: Discussionmentioning
confidence: 99%
“…Soluble ECM ligands also induce intracellular signaling and modulate cell behavior in solid tumors. Soluble ColI has been shown to influence TGF␤ receptor signaling and gene expression in breast cancer cells (38,39), and soluble integrin ligands such as ColI also rescue neuroblastoma cells from apoptosis under nonadherent conditions (40). ECM remodeling and degradation by metalloproteinases, which is associated with cancer growth and invasion, is likely to lead to the release of ECM components that can act as "soluble" pep- tides within the tumor microenvironment.…”
Section: Discussionmentioning
confidence: 99%
“…In vivo experiments revealed that collagen 2 interacts with the integrin α2β1 complex [30]. These integrin-type collagen receptors, α1β1, α2β1, α10β1, and α11β1, are involved in cancer progression and invasion.…”
Section: Collagen Receptorsmentioning
confidence: 99%
“…Besides the biochemical properties of cells described under invasion modes section, the expression of integrins has long been discussed to play a role in cell invasion. It has been described that the ECM regulates gene expression through focal adhesion-dependent integrin receptor signaling [72]. Several reports show a correlation of integrin expression and cellular invasiveness.…”
Section: Invasion Modes Regulate Cancer Cell Motilitymentioning
confidence: 99%